2001
DOI: 10.1128/mcb.2001.21.4.1336-1344.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SM22α-Deficient Mice Reveals Unanticipated Insights into Smooth Muscle Cell Differentiation and Function

Abstract: SM22␣ is a 22-kDa smooth muscle cell (SMC) lineage-restricted protein that physically associates with cytoskeletal actin filament bundles in contractile SMCs. To examine the function of SM22␣, gene targeting was used to generate SM22␣-deficient (SM22 ؊/؊LacZ ) mice. The gene targeting strategy employed resulted in insertion of the bacterial lacZ reporter gene at the SM22␣ initiation codon, permitting precise analysis of the temporal and spatial pattern of SM22␣ transcriptional activation in the developing mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
0
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(142 citation statements)
references
References 44 publications
8
126
0
6
Order By: Relevance
“…On Western blot analysis of GR protein from hearts of control and Sm-22 Creϩ GR loxP/loxP mouse pairs, we found that, if anything, heart GR was slightly increased and certainly not decreased in Sm-22 Creϩ GR loxP/loxP mice ( Figure 4B), suggesting that there was no significant GR deletion from cardiac myocytes in our KO mice. Consistent with this and previous studies, 15,16 we found no differences in heart rate between the two groups either before or after DEX administration ( Figure 5). Our data suggest a critical role of VSM GR on the acute hypertensive response to GC.…”
Section: No Apparent Role For Vsm Gr In Basal Bp Regulationsupporting
confidence: 93%
“…On Western blot analysis of GR protein from hearts of control and Sm-22 Creϩ GR loxP/loxP mouse pairs, we found that, if anything, heart GR was slightly increased and certainly not decreased in Sm-22 Creϩ GR loxP/loxP mice ( Figure 4B), suggesting that there was no significant GR deletion from cardiac myocytes in our KO mice. Consistent with this and previous studies, 15,16 we found no differences in heart rate between the two groups either before or after DEX administration ( Figure 5). Our data suggest a critical role of VSM GR on the acute hypertensive response to GC.…”
Section: No Apparent Role For Vsm Gr In Basal Bp Regulationsupporting
confidence: 93%
“…8g), in agreement with their pericyte origin and smooth muscle fate. This was confirmed by staining with an antibody recognizing the cytoskeletal protein SM22α, a smooth muscle-specific marker 24 (Fig. 8h); very few clones (less than 1%) contained both MyHC + and SM22α + cells (Fig.…”
Section: Ap + Cells Generate Smooth or Skeletal Myogenic Clones In VImentioning
confidence: 65%
“…27 While the analysis of transgelin-deficient mice demonstrated no developmental or basal homeostatic functions of transgelin in smooth muscle cells, 27 further studies implicate a critical role under pathophysiological settings. 28 In hypercholesterolemic ApoE-deficient mice, the lack of transgelin resulted in increased atherosclerotic lesion area and a higher proportion of proliferating smooth muscle cell-derived plaque cells.…”
Section: Transgelin In Glomerular Regeneration C Daniel Et Almentioning
confidence: 99%